2018
DOI: 10.1158/1535-7163.mct-16-0922
|View full text |Cite
|
Sign up to set email alerts
|

JQ1 Induces DNA Damage and Apoptosis, and Inhibits Tumor Growth in a Patient-Derived Xenograft Model of Cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is a fatal disease with a 5-year survival of <30%. For a majority of patients, chemotherapy is the only therapeutic option, and virtually all patients relapse. Gemcitabine is the first-line agent for treatment of CCA. Patients treated with gemcitabine monotherapy survive ∼8 months. Combining this agent with cisplatin increases survival by ∼3 months, but neither regimen produces durable remissions. The molecular etiology of this disease is poorly understood. To facilitate molecular char… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 48 publications
(82 reference statements)
2
25
0
Order By: Relevance
“…PDXs often maintain the cellular and histopathological structures of the original tumors (Table 1) [7][8][9]. Furthermore, cytogenetic analysis of tumor cells from PDXs has revealed significant preservation of the genomic and gene expression profiles between PDXs and parental patient tumors [10][11][12][13][14]. Notably, sensitivity to standard chemotherapeutics in PDXs closely correlates with clinical data in patients from which the PDXs are derived [12,13,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 95%
“…PDXs often maintain the cellular and histopathological structures of the original tumors (Table 1) [7][8][9]. Furthermore, cytogenetic analysis of tumor cells from PDXs has revealed significant preservation of the genomic and gene expression profiles between PDXs and parental patient tumors [10][11][12][13][14]. Notably, sensitivity to standard chemotherapeutics in PDXs closely correlates with clinical data in patients from which the PDXs are derived [12,13,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 95%
“…24 Recent reports proposed that JQ1, a selective inhibitor of BET proteins, exerts antigrowth effects in many types of cancer, inducing cell cycle arrest in cancer cells followed by the downregulation of the MYC oncogene. [25][26][27][28][29][30] However, the efficacy of JQ1 for BTC remains unknown. 30 In the present study, we investigated the therapeutic efficacy of JQ1 for ICC cells and identified the possible involvement of mutant IDH1 in the sensitivity to JQ1.…”
Section: Tp53mentioning
confidence: 99%
“…Bromodomain and extraterminal domain (BET) family proteins (BRD2, BRD3, BRD4, and BRDT) recognize acetylated lysine residues on histone tails and facilitate transcriptional activation through the recruitment of transcriptional regulatory complexes . Recent reports proposed that JQ1, a selective inhibitor of BET proteins, exerts antigrowth effects in many types of cancer, inducing cell cycle arrest in cancer cells followed by the downregulation of the MYC oncogene . However, the efficacy of JQ1 for BTC remains unknown .…”
Section: Introductionmentioning
confidence: 99%
“…Bromodomains participate in the spermatogenesis control system [42]. Studies of this process using bromodomain inhibitors i.e., highly specific JQ1, showed that it suppressed the expression of many genes that play essential roles in germ cells [24,43,44]. This inhibitor does not affect the proliferative properties of spermatogonia, but influences later stages of their development, spermatocytes and spermatids [37].…”
Section: Discussionmentioning
confidence: 99%